Pengembangan Studi Gasifikasi Tongkol Jagung Untuk Meningkatkan Performa Reaktor Downdraft Dengan Masukan Dua Udara Bertingkat - Irawan, Ibnu; Amir, Nizar; Budiarto, Khairil (Rekayasa, 2021)
Gasification is a technology for converting solid biomass into syngas. Corn cobs biomass is converted into pellets to obtain more homogeneous fuel. The downdraft gasifier type is used to have low tar content. The research was conducted to see the effect of the ratio of air and ER on the reactor temperature and the gas composition of CO, H2 and CH4. For pyrolysis and oxidation zones, air enters with variations (AR.Pir-Ox), namely 0%; 70%; 80%; and 90% in the intake air 14.5; 19.3; and 24.1 Nm3 / hr of E.R 0.3, 0.4, and 0.5. The air intake for each zone is regulated using a tap. Temperature measurement using type K thermocouple. Downdraft reactor performance is obtained by looking at the syngas content in CO, H2, and CH4 meters. The results showed the effect of AR.Pir-Oks with an air input of 24.10 Nm3 /h with E.R 0.5 having the highest temperature of 910oC, in the oxidation zone. This stratified air input plays a role in increasing the temperature along the altitude zone. The increase in the introduced oxygen produces an increase in heat. Syngas production in an air flow of 19.3 Nm3 / hour with a ratio of 90% pyrolysis and oxidation zone (ARPir-Oks), is the reactor produces gas products with a composition of 22.5% CO, 0.96% CH4, and 15.55 H2 %. The results of this test prove that the air entering the pyrolysis zone can provide additional syngas composition.